Advokasi Transnational UN Women terhadap Kekerasan Berbasis Gender Online di Indonesia (2021-2023): Analisis Transnational Advocacy Network (TANs) - Rahmat, Maura Putri; Santoso , Made Panji Teguh (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2025)
Reports from SAFEnet and Komnas Perempuan indicate a significant increase in Online Gender-Based Violence (OGBV) in Indonesia during 2021-2023. This study addresses the previously under-researched role of UN Women, employing a qualitative case study based on reports from UN Women, Komnas Perempuan, SAFEnet, and government policies. Through Keck and Sikkink's Transnational Advocacy Networks (TANs) framework, this research delineates UN Women's transnational advocacy mechanisms through four core strategies: information, symbolic, leverage, and accountability politics. UN Women functions as a strategic connector that consolidates discourse and pressure across diverse actors disseminating campaigns (#WTFMedia, #OrangeChallenge), partnering with Meta and TikTok, and supporting the passage of the 2022 Sexual Violence Crime Law (UU TPKS). However, its effectiveness is constrained by patriarchal norms, weak law enforcement, and regulatory disharmony. Theoretically, this study expands the application of TANs to intergovernmental organizations, demonstrating that transnational advocacy mechanisms can operate from within global institutional structures, not solely from civil society.